Hierarchical models, conditional independence and data augmentation - Allenby, Greg M. (Henry Stewart Talks, 2010)
Fly fishing: a hierarchical model, Motivation, Traditional estimation, Gibbs sampler for the probit model, Probit conditional distributions, Inverse cdf, Basics of hierarchical models, Conditional independence, Mixtures of normals, Model hierarchy, Gibbs sampler for mixtures of normals, Multivariate mix of norms Ex